ANALYSIS OF CONTRACT CHANGE ORDER (CCO) COSTS IN BUILDING CONSTRUCTION PROJECTS - Pratondo W, Wahyu; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
In project implementation, change orders frequently arise post-contract signing between the owner and contractor. These changes often stem from design modifications or budget adjustments by the owner. Contractor-initiated change orders result from disparities between design plans and bill of quantities, insufficient design details, impractical field conditions, complex design execution, and challenges in material mobilization. Poorly managed change orders can lead to increased costs, delays, and diminished contractor performance. To mitigate change orders, this study employs change order correlation analysis using original data, evaluating change order ratio (COR), change order ratio in addition (CORA), and change order ratio in subtraction (CORS). Analyzing six construction projects, the study concludes that the average Change Order Ratio Index (COR) is 26%, indicating a 26% change from the original contract value. The average Change Order Ratio in Addition (CORA) is 16%, signifying 16% of changes result from additional work. The average Change Order Ratio in Subtraction (CORS) is 10%, indicating 10% of changes stem from work being less than the original contract value.